Kodeks karny wykonawczy : Język kodeksu, sposób uregulowania oraz odesłania pozaprawne - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The study presents specific features of the language of the provisions of the Executive Penal Code. The Executive Penal Code contains numerous vague and indistinct phrases, creating space for their interpretation. General clauses, the scope of discretion of the enforcement proceedings bodies in issuing resolutions or decisions, undefined phrases, estimated phrases and prognostic phrases are often interpretive laxities intended by the legislator, the specification of which should only take place in a specific process of applyingthe law by means of operative interpretation.
Keywords: Executive Penal Code; general clauses; estimates; forecast